A critical analysis of the alternative treatments applied to effluents from Brazilian textile industries. (October 2021) - Ramos, Márcio Daniel Nicodemos; Lima, Juan Pablo Pereira; de Aquino, Sérgio Francisco; Aguiar, André
Abstract: The textile industry wastewater is highly harmful to the environment when it is discharged in its raw state, since it might contain dyes, surfactants, and other dissolved compounds that adversely affect the aquatic ecosystems. Based on the low biodegradability of textile effluents, physicochemical processes (e.g. coagulation-flocculation) are usually indicated and eventually combined with biological treatment, which is applied at full scale due to lower costs. However, the conventional processes have limitations, of which it can highlight the low color removal and formation of residual sludge. The present work consists of a critical analysis about the alternative processes evaluated to treat effluents generated by mills of the Brazilian textile sector, an important industrial segment of this country. It was verified that the advanced oxidation processes (AOPs), as the electrooxidation, photo-Fenton and classical Fenton oxidation have been the most effective in reducing color (average above 90%), and organic matter (average above 78%) from such effluents. In addition, coagulation-flocculation with plant-derived inputs, electrocoagulation and unconventional bacterial systems are alternatives that have also been quite efficient. Analyzing the characteristics of secondary effluents of biological systems normally used to treat textile effluents, it was observed that some still have relevant concentrations of pollutants. Therefore, AOPs have been also evaluated as a polishing step to treat them, which were effective to comply with the Brazilian environmental agencies for its disposal in water bodies. Some works described the possibility of reusing the treated effluents, showing that many of the alternative processes are also promising in this regard. Graphical abstract: Unlabelled Image Highlights: Alternative processes were tested to treat textile effluents generated in Brazilian mills. Natural inputs can decrease the requirement for conventional chemicals in coagulation-flocculation. Eletrooxidation, Photo-Fenton and classical Fenton oxidation were the most effective treatments. Advanced oxidation processes have been efficient as a polishing step to abide the legislation. Textile effluents treated through alternative processes can be suitable to industrial reuse.